Preparation method of lignin nanoparticle colloidal dispersion and application thereof

CN116284847BActive Publication Date: 2026-10-09NANJING FORESTRY UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310361621.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-06
Publication Date
2026-10-09
Estimated Expiration
2043-04-06

AI Technical Summary

Technical Problem

但由于木质素的粒径、形貌、润湿性、稳定性等因素对Pickering乳液稳定性的影响并不明确,很难制备性能稳定的Pickering乳液,因此,开发一种能够制备性能稳定的木质素粒子稳定的Pickering乳液具有尤其重要的意义

Benefits of technology

[0022] Beneficial Effects: Compared with the prior art, the technical solution of the present invention has the following beneficial effects: The present invention classifies lignin by stepwise dissolution and then obtains lignin nanoparticles with different morphologies, particle sizes, and polarities by antisolvent precipitation. The lignin nanoparticles in supernatant 1 have the highest polarity and are suitable for use as surfactants; the lignin nanoparticles in supernatant 2 have the lowest polarity and can form hollow spherical particles, which are suitable for encapsulation and sustained release. The lignin nanoparticles in solution 3 have moderate polarity and the largest proportion, and the solid particles formed are small and uniform in size, which is suitable for use in Pickering emulsions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116284847B_ABST
    Figure CN116284847B_ABST
Patent Text Reader

Abstract

The application discloses a preparation method of a lignin nanocolloid dispersion liquid with uniform size and good stability and application thereof, relates to the technical field of nanometer materials, and selects two solvents, i.e., water and tetrahydrofuran, and a cosolvent formed by the two solvents, carries out grading on lignin through a step-by-step dissolution mode, obtains lignin nanoparticles with different morphologies and particle diameters by using a reverse-solvent precipitation mode, and finally selects the lignin nanoparticles with optimal morphologies / size to prepare Pickering emulsions with excellent stability. The application realizes the grading of lignin and the preparation of the nanoparticles by using less organic solvents, optimizes the operation process compared with other grading methods, and avoids the process of drying and resolubilizing the lignin after grading. A large amount of organic solvents is avoided in the lignin grading process, and the harm to human bodies and the environment is reduced. The application solves the problems of the prior art, such as a complex lignin nanoparticle preparation method, a large amount of solvents, and non-uniform particle size.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of nanomaterials technology, and more specifically, to a method for preparing lignin nanoparticles with uniform size and good stability, and their application. Background Technology

[0002] In recent years, with the development of nanoscience and technology, lignin nano-sizing can effectively overcome the inherent heterogeneity, poor dispersibility, and large particle size of its structure, providing a new approach for the development and utilization of lignin resources. Compared with lignin macromolecules, nano-sized lignin has ultra-high reactivity, a large specific surface area, ultra-high surface energy and surface tension. The particle size of lignin nanoparticles is controllable, the structure is uniform, the water dispersibility is good, and it has abundant functional groups and strong reactivity.

[0003] Currently, common methods for preparing lignin nanoparticles include acid precipitation, solvent exchange, mechanical methods, and interfacial polymerization. Acid precipitation involves continuously lowering the pH of a lignin solution, causing lignin to gradually precipitate and form lignin particles. This method is simple and easy to operate, but the resulting particles are of uneven size, have uncontrollable morphology, and exhibit low purity. Mechanical methods apply external mechanical shearing to break down large particles into smaller ones. This is a green and environmentally friendly method, but it consumes a lot of energy, and the structure and size of the resulting lignin particles are unstable. Interfacial polymerization involves polymerization or cross-linking reactions occurring at the interface of two immiscible materials. This method is commonly used to prepare lignin nanocapsules, but the reactions involved are complex, and many chemicals are used. Solvent exchange is currently the most commonly used method for preparing spherical lignin nanoparticles. This method utilizes the difference in solubility of lignin in good solvents (usually THF and acetone) and antisolvents (usually water). The lignin is first dissolved in an organic solvent, and then the solution is passed into the antisolvent under certain conditions. The lignin nanoparticles are obtained by aggregation in the antisolvent. The lignin nanoparticles prepared by this method are regular spherical, have high stability, and are simple to operate under mild conditions.

[0004] However, in the process of preparing lignin nanoparticles by solvent exchange, the inherent structural differences of lignin are often overlooked. Lignin cannot be completely dissolved in THF, and the dissolved portion is the lower molecular weight fraction, resulting in lignin nanoparticles with low yield, wide particle size distribution, and significant morphological variations. Although recent studies have shown that using organic solvents to fractionate lignin before antisolvent preparation improves particle uniformity, the stepwise fractionation method makes the nanoparticle formation process particularly complex. Moreover, the more solvents involved, the lower the yield of each component, hindering the effective and efficient utilization of each component. Furthermore, the large amount of organic solvents used is not only harmful to the environment and human health but also still faces the problem of low solubility of lignin in good solvents.

[0005] In recent years, the application of lignin in Pickering emulsions has become a focus of research both domestically and internationally. However, since the effects of lignin particle size, morphology, wettability, and stability on the stability of Pickering emulsions are not clearly defined, it is difficult to prepare stable Pickering emulsions. Therefore, developing a method to prepare stable lignin-particle-stabilized Pickering emulsions is of particular importance. Summary of the Invention

[0006] Technical problem: In order to overcome the above-mentioned defects of the prior art, the purpose of this invention is to provide a method for preparing a colloidal dispersion of lignin nanoparticles with uniform size and good stability.

[0007] Another object of the present invention is to provide a method for preparing a Pickering emulsion with stable performance.

[0008] To solve the above-mentioned technical problems, the technical solution of the present invention is as follows: A method for preparing a colloidal dispersion of lignin nanoparticles with uniform size and good stability, comprising the following steps:

[0009] (1) Dissolve sulfate lignin in water, control the solid-liquid ratio of sulfate lignin to water to be 1:20-1:80, sonicate for 30-80 min, and then centrifuge (centrifuge speed is 8000-10000 rpm, centrifuge for 10-30 min) to obtain supernatant 1 and precipitate 1. At this time, the supernatant contains the most hydrophilic sulfate lignin.

[0010] (2) Heat and evaporate the supernatant 1 to obtain a lignin dispersion with a concentration of 0.1%-1%;

[0011] (3) After the precipitate 1 in step (1) is completely dried, it is dissolved in THF with a solid-liquid ratio of 1:20-1:80. After ultrasonic treatment for 30-80 min, the precipitate 1 is fully dissolved and then centrifuged (centrifugation speed is 8000-10000 rpm, centrifugation for 10-30 min) to obtain supernatant 2 and precipitate 2. At this time, the supernatant is dissolved in the most hydrophobic sulfate lignin. This part of lignin is not conducive to the preparation of stable Pickering emulsion.

[0012] (4) Concentrate the supernatant 2 in step (3) to a concentration of 1-50 mg / ml, then add 4 times the volume of water while stirring, continue magnetic stirring and let it evaporate naturally for 24-48 hours, then heat to evaporate the residual THF and some water to obtain a lignin nanoparticle colloidal dispersion with a concentration of 0.1%-1%.

[0013] (5) After the precipitate 2 from step (3) is completely dried, it is dissolved in a THF / water (vTHF / vwater = 7 / 3) mixed solvent with a solid-liquid ratio of 1:20-1:80. The mixture is ultrasonically treated for 30-80 minutes. After complete dissolution, it is centrifuged (centrifugation speed is 8000-10000 rpm, centrifugation time is 10-30 minutes) to obtain a completely dissolved solution 3.

[0014] (6) Concentrate the solution 3 from step (5) to a concentration of 1-50 mg / ml, then add it to 4 times the volume of water instantly while stirring. Continue to stir magnetically and allow it to evaporate naturally for 24-48 hours. Then heat to evaporate the residual THF and some water to obtain a lignin nanoparticle colloidal dispersion with a concentration of 0.1%-1%.

[0015] Preferably, rotary evaporation is used in steps (2), (4) and (6), and the evaporation temperature is 30-80℃.

[0016] This invention also provides a method for preparing a stable Pickering emulsion, comprising the following steps:

[0017] (7) Using the lignin nanoparticle colloidal dispersion obtained in steps (1)-(6) above, the oil phase is mixed at a certain volume ratio and emulsified by an emulsification device to obtain Pickering emulsions with different grades of lignin particle stability.

[0018] Furthermore, the volume ratio of the lignin nanoparticle colloidal dispersion to the oil phase is 1:(1-3).

[0019] Furthermore, the oil phase used is one of sunflower seed oil, paraffin, toluene, edible oil, cyclohexane, and chloroform.

[0020] Furthermore, the emulsification equipment is a high-speed shear emulsifier with an emulsification speed of 12,000-16,000 rpm and an emulsification time of 1-10 min.

[0021] For lignin-stabilized Pickering emulsions, the key factors affecting stability are the size and surface hydrophilic / hydrophobic properties of the lignin particles. Lignin is a relatively complex polymer with diverse surface chemical functional groups and a wide molecular weight, leading to significant differences in its affinity for different solvents. Hydrophobic interactions are one of the primary driving forces in the preparation of nanoparticles using nanoprecipitation methods, and larger molecular weight lignin results in smaller nanoparticles. Based on this principle, water and tetrahydrofuran were selected as solvents to separate the most hydrophilic (component F1) and most hydrophobic (component F2) fractions of the lignin composition through a stepwise dissolution method. This reduced the heterogeneity of lignin while yielding a high-molecular-weight lignin component (component F3) with intermediate hydrophilic / hydrophobic properties. Using water as the antisolvent, components F2 and F3 were nano-sized to obtain the corresponding lignin nanoparticles. The different surface wettability of the lignin nanoparticles resulted in varying adsorption stability at the oil-water interface, ultimately leading to Pickering emulsions with different stabilities.

[0022] Beneficial Effects: Compared with the prior art, the technical solution of the present invention has the following beneficial effects: The present invention classifies lignin by stepwise dissolution and then obtains lignin nanoparticles with different morphologies, particle sizes, and polarities by antisolvent precipitation. The lignin nanoparticles in supernatant 1 have the highest polarity and are suitable for use as surfactants; the lignin nanoparticles in supernatant 2 have the lowest polarity and can form hollow spherical particles, which are suitable for encapsulation and sustained release. The lignin nanoparticles in solution 3 have moderate polarity and the largest proportion, and the solid particles formed are small and uniform in size, which is suitable for use in Pickering emulsions.

[0023] This invention uses THF as both the organic solvent for grading and the organic solvent for dissolving lignin in the anti-solvent process, allowing the grading and nano-sizing processes to be combined into one. Compared with other grading methods, this avoids the process of drying and re-dissolving lignin after grading, thus optimizing the operation process. It also avoids the use of large amounts of organic solvents, reducing harm to human health and the environment.

[0024] This invention screened out the optimal lignin nanoparticles to prepare a lignin nanoparticle-stabilized Pickering emulsion with superior stability. Attached Figure Description

[0025] Figure 1 This is a flowchart of the experimental process of the present invention.

[0026] Figure 2 Lignin nanoparticles were prepared by fractionation of lignin followed by anti-solvent precipitation. (a1) Morphology and particle size distribution of all components. (a2) Morphology and particle size distribution of component 1. (a3) ​​Morphology and particle size distribution of component 2. (a4) Morphology and particle size distribution of component 3.

[0027] Figure 3 : Air-water and oil-water interfacial properties of lignin nanoparticles with three components. (a) Surface activity of lignin nanoparticles with three components; (b1-b3) Water contact angle of lignin nanoparticles with three components; (c) Oil-water interfacial activity of lignin nanoparticles with three components; (d1-d3) Three-phase contact angle of lignin nanoparticles with three components.

[0028] Figure 4 Stability of Pickering emulsions stabilized by three components of lignin nanoparticles. (a) Emulsion freshly prepared and emulsion after 30 days; (b) Instability index of Pickering emulsions stabilized by three components of lignin nanoparticles; (c) Droplet morphology of Pickering emulsions stabilized by three components of lignin nanoparticles after 30 days.

[0029] Figure 5 Adsorption behavior of three lignin nanoparticles at the sunflower seed oil / water interface. (a) Frequency versus time during adsorption and desorption; (b) Dissipation versus time during adsorption and desorption; (c) Dissipation versus frequency during adsorption and desorption. Detailed Implementation

[0030] The technical solution of the present invention will now be described in detail with reference to the accompanying drawings.

[0031] Analysis of the adsorption mechanism of lignin nanoparticles with different components:

[0032] Sunflower seed oil was dissolved in chloroform to prepare a concentration of 0.1%-1%. 100 μL of the solution was spin-coated onto gold flakes at a speed of 2000-5000 rpm for 30 s-1 min. The prepared gold flakes were then placed in a QCM module, and a colloidal dispersion of lignin nanoparticles containing different components was passed through for adsorption analysis.

[0033] Comparative example:

[0034] Take 10g of ungraded sulfate lignin and add it to 200ml of a THF / water mixture (140ml THF, 60ml water). Sonicate for 80min until completely dissolved, then add to 800ml of water. Stir magnetically at 600rpm for 48h to evaporate. Remove residual THF by rotary evaporation at 40℃. This is the colloidal solution F0 containing all components of lignin nanoparticles. The morphology and particle size distribution of the lignin nanoparticles are shown in the figure. Figure 1 (a1) As can be seen from the figure, the morphology and size of the lignin nanoparticles prepared from all components are not uniform.

[0035] Water was added to adjust the mass concentration of lignin nanoparticles to 0.1-1%. The colloidal solution and sunflower seed oil were mixed at a volume ratio of 5 ml:5 ml, and the two phases were emulsified using a high-speed shear emulsifier. The speed was set to 12000 rpm and the emulsification time was 1 min to obtain a stable Pickering emulsion of lignin nanoparticles.

[0036] Example 1

[0037] 10g of unfractionated sulfate lignin was dissolved in 200ml of water and sonicated for 80min. After complete dissolution, the solution was centrifuged at 8000-10000rpm for 10-30min to separate the supernatant 1 and precipitate 1. The supernatant was dried and weighed to 0.94g, which is component F1. 0.5g of component F1 lignin was taken and dissolved in an appropriate amount of water by sonication for 30min. A 0.1-1% colloidal solution of component F1 lignin nanoparticles was obtained.

[0038] Dissolve 9.06 g of dried precipitate 1 in 181 ml of THF, sonicate for 80 min, and centrifuge at 8000-10000 rpm for 10-30 min to separate supernatant 2 and precipitate 2. Concentrate supernatant 2 to a concentration of 10 mg / ml, add 4 times the volume of water to supernatant 2, and evaporate magnetically at 400 rpm for 24 h. Remove residual THF by rotary evaporation at 30℃. This is the F2 lignin nanoparticle colloidal solution. Adjust its concentration to 0.1-1% by adding appropriate amount of water.

[0039] After completely drying precipitate 2, weigh it to 6.6g. This is component F3 lignin. Take 1g of component F3 and add it to 100ml of THF / water (70ml THF, 30ml water) mixed solution. Sonicate for 80min to dissolve it completely, then add 4 times the volume of water. Stir magnetically at 400rpm for 24h to evaporate. Remove residual THF by rotary evaporation at 40℃. This is component F3 lignin nanoparticle colloidal solution. Add water as needed to adjust its concentration to 0.1-1%.

[0040] Example 2

[0041] 10g of unfractionated sulfate lignin was dissolved in 500ml of water and sonicated for 60min. After complete dissolution, the solution was centrifuged at 8000-10000rpm for 10-30min to separate the supernatant 1 and precipitate 1. Supernatant 1 is component F1. 0.5g of component F1 lignin was taken and dissolved in an appropriate amount of water by sonication for 60min. A 0.1-1% colloidal solution of component F1 lignin nanoparticles was obtained.

[0042] Dissolve 9.06 g of dried precipitate 1 in 453 ml of THF, sonicate for 60 min, and centrifuge at 8000-10000 rpm for 10-30 min to separate supernatant 2 and precipitate 2. Concentrate supernatant 2 to a concentration of 20 mg / ml, add 4 times the volume of water to supernatant 2, and evaporate magnetically at 600 rpm for 32 h. Remove residual THF by rotary evaporation at 40℃. This is the F2 lignin nanoparticle colloidal solution. Adjust its concentration to 0.1-1% by adding water as needed.

[0043] After completely drying precipitate 2, weigh it to 6.6g. This is component F3 lignin. Take 1g of component F3 and add it to 50ml of THF / water (35ml THF, 15ml water) mixed solution. Sonicate for 60min to dissolve it completely, then add 4 times the volume of water. Stir magnetically at 600rpm for 32h to evaporate. Remove residual THF by rotary evaporation at 40℃. This is component F3 lignin nanoparticle colloidal solution. Add water as needed to adjust its concentration to 0.1-1%.

[0044] Example 3

[0045] 10g of unfractionated sulfate lignin was dissolved in 500ml of water and sonicated for 60min. After complete dissolution, the solution was centrifuged at 8000-10000rpm for 10-30min to separate the supernatant 1 and precipitate 1. Supernatant 1 is component F1. 0.5g of component F1 lignin was taken and dissolved in an appropriate amount of water by sonication for 60min. A 0.1-1% colloidal solution of component F1 lignin nanoparticles was obtained.

[0046] Dissolve 9.06 g of dried precipitate 1 in 453 ml of THF, sonicate for 60 min, and centrifuge at 8000-10000 rpm for 10-30 min to separate supernatant 2 and precipitate 2. Concentrate supernatant 2 to a concentration of 1 mg / ml, add 4 times the volume of water to supernatant 2, and evaporate magnetically at 600 rpm for 32 h. Remove residual THF by rotary evaporation at 40℃. This is the F2 lignin nanoparticle colloidal solution. Adjust its concentration to 0.1-1% by adding appropriate amount of water.

[0047] After completely drying precipitate 2, weigh it to 6.6g. This is component F3 lignin. Take 1g of component F3 and add it to 1000ml of THF / water (700ml THF, 300ml water) mixed solution. Sonicate for 60min to dissolve it completely, then add 4 times the volume of water. Stir magnetically at 600rpm for 32h to evaporate. Remove residual THF by rotary evaporation at 40℃. This is component F3 lignin nanoparticle colloidal solution. Add water as needed to adjust its concentration to 0.1-1%.

[0048] Example 4

[0049] 10g of unfractionated sulfate lignin was dissolved in 800ml of water and sonicated for 30min. After complete dissolution, the solution was centrifuged at 8000-10000rpm for 10-30min to separate the supernatant 1 and precipitate 1. Supernatant 1 is component F1. 0.5g of component F1 lignin was taken and dissolved in an appropriate amount of water by sonication for 30min. This yielded a 0.1-1% colloidal solution of component F1 lignin nanoparticles.

[0050] Dissolve 9.06g of dried precipitate 1 in 725ml of THF, sonicate for 30min, and centrifuge at 8000-10000rpm for 10-30min to separate supernatant 2 and precipitate 2. Concentrate supernatant 2 to a concentration of 50mg / ml, add 4 times the volume of water to supernatant 2, and evaporate magnetically at 800rpm for 48h. Remove residual THF by rotary evaporation at 40℃. This is the F2 lignin nanoparticle colloidal solution. Adjust its concentration to 0.1-1% by adding water as needed.

[0051] After completely drying precipitate 2, weigh it to 6.6g. This is component F3 lignin. Take 1g of component F3 and add it to 20ml of THF / water (14ml THF, 6ml water) mixed solution. Sonicate for 30min to dissolve it completely, then add 4 times the volume of water. Stir magnetically at 800rpm for 48h to evaporate. Remove residual THF by rotary evaporation at 40℃. This is component F3 lignin nanoparticle colloidal solution. Add water as needed to adjust its concentration to 0.1-1%.

[0052] Example 5

[0053] Take 5 ml of colloidal solution containing F1, F2 and F3 lignin nanoparticles and mix it with 5 ml of sunflower seed oil. Then, emulsify the two phases using a high-speed shear emulsifier. Set the speed to 12000 rpm and the emulsification time to 1 min to obtain a stable Pickering emulsion of lignin nanoparticles.

[0054] Example 6

[0055] Take 5 ml of colloidal solution containing F1, F2 and F3 lignin nanoparticles and mix it with 10 ml of sunflower seed oil. Then, emulsify the two phases using a high-speed shear emulsifier. Set the speed to 14000 rpm and the emulsification time to 3 min to obtain a stable Pickering emulsion of lignin nanoparticles.

[0056] Example 7

[0057] Take 5 ml of colloidal solution containing F1, F2 and F3 lignin nanoparticles and mix it with 15 ml of sunflower seed oil. Then, emulsify the two phases using a high-speed shear emulsifier. Set the speed to 16000 rpm and the emulsification time to 10 min to obtain a stable Pickering emulsion of lignin nanoparticles.

[0058] Furthermore, the present invention is suitable for lignin from different sources and types.

[0059] Furthermore, sunflower seed oil can be replaced with one of the following: paraffin, toluene, edible oil, cyclohexane, and chloroform.

[0060] like Figure 2-5 The average particle size of lignin particles in F1 is 190 nm, and the lignin molecules aggregate to form an irregular morphology. Figure 2 It has very strong hydrophilicity and surface / interfacial activity. Figure 3 The yield is relatively low, only about 10%. A relatively stable Pickering emulsion can be prepared. Figure 4 F1 forms reversible adsorption at the oil-water interface, similar to the adsorption characteristics of polymeric surfactants. Figure 5 Therefore, it is suitable as a surfactant. The average particle size of the lignin particles in F2 is 146 nm, and the lignin molecules self-assemble into regular spherical particles with a hollow structure. Figure 2 It has the strongest hydrophobicity and relatively weak surface / interfacial activity. Figure 3 The yield was around 20%. Although the prepared Pickering emulsion exhibited good macroscopic stability, droplets were very prone to coalescence, leading to phase separation and eventual instability. Figure 4 Only a small portion of the F2 particles adsorb at the oil-water interface, while the majority desorb from the interface, resulting in the least stable Pickering emulsion. Figure 5 The average particle size of the lignin particles in F3 is 39 nm, with the smallest particle size and uniform, regular spherical shape. Figure 2 This part has the highest yield, reaching 70%. Particles with relatively uniform morphology and size possess suitable hydrophilicity and lipophilicity, and have almost no surface activity. Figure 3 However, the resulting emulsion is the most stable. Figure 4 Most F3 particles are irreversibly adsorbed at the oil-water interface, forming a stable particle film, making F3 particles the best choice for Pickering emulsions. F0 particles contain three components, F1-F3, with F3 being the most abundant. Therefore, their morphology, particle size, and emulsion stability are similar but not as good as F3.

[0061] The foregoing has shown and described the basic principles, main features, and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the specific embodiments described above. The specific embodiments and descriptions in the specification are merely for further illustrating the principles of the invention. Various changes and modifications can be made to the present invention without departing from its spirit and scope, and all such changes and modifications fall within the scope of the present invention as claimed. The scope of protection of the present invention is defined by the claims and their equivalents.

Claims

1. A method for preparing a lignin nanoparticle colloidal dispersion, characterized in that, Includes the following steps: (1) Dissolve sulfate lignin in water, sonicate, and after complete dissolution, centrifuge at 8000-10000 rpm for 10-30 min to obtain supernatant 1 and precipitate 1; (2) Heat and evaporate the supernatant 1 to obtain a 0.1%-1% lignin dispersion F1; (3) After the precipitate 1 in step (1) is completely dried, it is dissolved in tetrahydrofuran (THF). After ultrasonic dissolution, it is centrifuged at 8000-10000 rpm for 10-30 min to obtain supernatant 2 and precipitate 2. (4) After concentrating the supernatant 2 in step (3), add four times the volume of water while stirring, and let it evaporate naturally under magnetic stirring. Then heat to evaporate the residual THF and some water to obtain a lignin nanoparticle colloidal dispersion F2 with a concentration of 0.1%-1%. (5) After the precipitate 2 from step (3) is completely dried, it is dissolved in a THF / water mixed solvent, where v THF / v water = 7 / 3; after ultrasonic dissolution, it is centrifuged at 8000-10000 rpm for 10-30 min to obtain a completely dissolved solution 3. (6) After concentrating the solution 3 from step (5), add it to four times the volume of water while stirring. Under the action of magnetic stirring, it will naturally evaporate. Then heat to evaporate the residual THF and some water to obtain a lignin nanoparticle colloidal dispersion F3 with a concentration of 0.1%-1%.

2. The method for preparing a lignin nanoparticle colloidal dispersion according to claim 1, characterized in that, The solid-liquid ratio in steps (1), (3) and (5) is 1:20-1:80 (w / v).

3. The method for preparing a lignin nanoparticle colloidal dispersion according to claim 1, characterized in that, The ultrasonic treatment time in steps (1), (3) and (5) is 30-80 min.

4. The method for preparing a lignin nanoparticle colloidal dispersion according to claim 1, characterized in that, The concentrations of supernatant 2 and solution 3 in steps (4) and (6) are 1-50 mg / ml.

5. A method for preparing a lignin nanoparticle colloidal dispersion according to claim 1, characterized in that, In steps (4) and (6), the natural evaporation time is 24-48h, the magnetic stirring speed is 400-800rpm, rotary evaporation is used, and the evaporation temperature is 30-80℃.

6. A method for preparing a stable Pickering emulsion, characterized in that, The process includes the following steps: mixing the colloidal dispersions of F1, F2 and F3 lignin nanoparticles prepared by the preparation method according to any one of claims 1-5 with the oil phase at a certain volume ratio, and emulsifying them using an emulsification device to obtain Pickering emulsions with different grades of lignin particle stability.

7. A method for preparing a stable Pickering emulsion according to claim 6, characterized in that, The volume ratio of the lignin nanoparticle colloidal dispersion to the oil phase is 1:(1-3).

8. A method for preparing a stable Pickering emulsion according to claim 6, characterized in that, The oil phase is one of paraffin, toluene, edible oil, cyclohexane, and chloroform.

9. A method for preparing a stable Pickering emulsion according to claim 6, characterized in that, The emulsification equipment is a high-speed shear emulsifier with an emulsification speed of 12,000-16,000 rpm and an emulsification time of 1-10 min.

Citation Information

Patent Citations

  • Lignin colloidal sphere nano-particles based on temperature-induced graded self-assembly and preparation method of lignin colloidal sphere nano-particles

    CN114854055A

  • Functionalization of cellulose with lignin to produce high-value products

    US20180327514A1